(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The article focuses on the functioning of the global and national tourism industry after the end of the COVID-19 pandemic and during the first two years of the Russian-Ukrainian war. The relevance of the work is enhanced by the fact that the tourism industry is the first to suffer in times of political and financial crises. But despite this, it is the most profitable in a period of stable functioning of state institutions that ensure overall economic growth. The paper analyzes the importance of stable functioning of the hospitality sector in wartime, further development of the hotel and restaurant business, search for ways to maximize profits, and rethinking the existing foreign experience of countries in the territory of which military operations took place, which had a devastating effect on the tourism sector. The development of domestic tourism requires the introduction of innovative approaches (development of new hiking routes, stabilization of mental health of military personnel undergoing rehabilitation, integration of IDPs into social and public life of large cities, reconstruction of old and promotion of new tourist locations in accordance with the needs of time and public demands, development of "memory routes") to expand the list of traditional services and introduction of digital technologies, which facilitates business and expands the range of future consumers.